2000
DOI: 10.1103/physrevb.61.16179
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transitions in single-walled carbon nanotubes: A resonance Raman study

Abstract: Resonance excitation profiles of the high-frequency peaks in the Raman spectra of single-walled carbon nanotubes normalized to the scattering intensity of CaF 2 are presented. We find separate resonances of metallic and semiconducting tubes throughout the visible and the near-IR excitation range. The resonance shift of samples with different mean diameters confirm the inverse proportionality of the resonant transition energy to the tube diameter. Smaller diameter tubes are found to have sharper resonances than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
39
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 19 publications
(23 reference statements)
6
39
1
Order By: Relevance
“…Semiconducting tubes have sharp G þ and G À , while metallic tubes have a broad down-shifted G À and a sharp G þ , [36][37][38][39][40][41][42][43][44] although some experiments seem to show that the G À peak appears only in nanotube bundles. 45) The G À band shows a strong diameter dependence, being lower in frequency for smaller diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Semiconducting tubes have sharp G þ and G À , while metallic tubes have a broad down-shifted G À and a sharp G þ , [36][37][38][39][40][41][42][43][44] although some experiments seem to show that the G À peak appears only in nanotube bundles. 45) The G À band shows a strong diameter dependence, being lower in frequency for smaller diameters.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity and frequency of the T band can, respectively, be used for estimating the SWNT yield in the carbon soot [13] and for evaluating the charge transfer between the tubes and a chemical dopant [14]. Furthermore, interesting resonance Raman effects due to size and helicity selection [15,16] and the metallic or semiconducting nature of the tubes have been reported [17][18][19][20]. It was shown that a diameter selective resonance [15] and a periodic oscillation in the frequency position [16] observed in the R band region are connected to the van Hove singularities in the one-dimensional (1D) electronic density of states of the SWNTs.…”
mentioning
confidence: 99%
“…Figure 4 displays the D Ã -band intensity, corrected for incident power and spectrometer sensitivity, as a function of E exc . A resonant excitation profile for the metallic SWNT ensemble in our sample, obtained from a single-resonance model [17], is also shown for comparison. The sharp drop of the D Ã -band intensity for E exc <1.75 eV clearly shows that DR is no more possible for a considerable part of the metallic SWNTs in the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The dashed line connecting experimental points is only a guide to the eye. The solid line (green) is a resonant Raman excitation profile of the examined metallic SWNT ensemble for a single-resonance process [17]. Table 1 DR phonon states of the TO branch as obtained from the blue-arrow process with phonon wave vector q 1 in Fig.…”
Section: Resultsmentioning
confidence: 99%